A case of Kawasaki disease with coexistence of a parapharyngeal abscess requiring incision and drainage - Se Hyun Choi; Hyun Jung Kim (Korean Pediatric Society, 2010)
Kawasaki disease (KD) causes multisystemic vasculitis but infrequently manifests with deep neck infections, such as a peritonsillar abscess, peritonsillar or deep neck cellulitis, suppurative parapharyngeal infection, or retropharyngeal abscess. As its etiology is still unknown, the diagnosis is usually made based on typical symptoms. The differential diagnosis between KD and deep neck infections is important, considering the variable head and neck manifestations of KD. There are several reports on KD patients who were initially diagnosed with retropharyngeal abscess on on computed tomography scans (CT). However, the previously reported cases did not have abscess or fluid collection on retropharyngeal aspiration. Therefore, false-positive neck CT scans have been obtained, until recently. In this case, suspected neck abscess in patients with KD unresponsive to intravenous immunoglobulin could signal the possible coexistence of suppurative cervical lymphadenitis.